Tax‐Avoidance Activities of U.S. Multinational Corporations* - Rego, Sonja Olhoft (Contemporary Accounting Research, 2003)
Abstract This paper investigates whether economies of scale exist for tax planning. In particular, do larger, more profitable, multinational corporations avoid more taxes than other firms, resulting in lower effective tax rates? While the empirical results indicate that, ceteris paribus, larger corporations have higher effective tax rates, firms with greater pre‐tax income have lower effective tax rates. The negative relation between effective tax rates (ETRs) and pretax income is consistent with firms with greater pre‐tax income having more incentives and resources to engage in tax planning. Consistent with multinational corporations being able to avoid income taxes that domestic‐only companies cannot, I find that multinational corporations in general, and multinational corporations with more extensive foreign operations, have lower worldwide ETRs than other firms. Finally, in a sample of multinational corporations only, I find that higher levels of U.S. pre‐tax income are associated with lower U.S. and foreign ETRs, while higher levels of foreign pre‐tax income are associated with higher U.S. and foreign ETRs. Thus, large amounts of foreign income are associated with higher corporate tax burdens. Overall, I find substantial evidence of economies of scale to tax planning.